THE 3P’S SUCCESS IN PUBLIC SPEAKING (DA’WAH) ON ISLAMIC EDUCATION - Abd. Aziz (Jurnal Bahasa Lingua Scientia, 2018)
The purpose of this paper is to share the findings of a quantitative research which aims at helping students to be better in Public Speaking (Da’wah). The first step is doing post-test in random students to know their capability on Public Speaking (Da’wah). Following this, treatment do by the researcher in 9 meeting and every meeting the students do 3P’s Success there are Preparation, Practice, Performance but the performance do in another day. After do the treatment the researcher does post-test to know is the treatment working on the students or not, the treatment does in the last 2 days in each day 10 students do the post-test individually in front of audience to know their skill are improve or not.